Kinetic studies on the anaerobic degradation of soluble and particulate matter in potato wastewater - Durruty, Ignacio (2012)
The anaerobic degradation of particulate-containing potato processing wastewater using a mixed culture from an industrial anaerobic wastewater treatment plant as inoculum was characterised and modelled. Anaerobic digestion is being increasingly used for wastewater treatment, particularly those which contain high levels of biodegradable matter such as potato processing effluents. A major prerequisite for its proper modelling is a reliable wastewater characterisation with a proper discrimination of the chemical oxygen demand (COD) fractions. These wastewaters contain both soluble (S ) and particulate (X ) organic load that are assimilated by microorganisms at different rates. Furthermore, these wastewaters generally contain both solid (XI) and soluble (SI) inert to anaerobic degradation fractions. In this work, a procedure to determine the COD fractions of potato wastewater is developed. For the wastewater studied, the initial fraction of inert particulate organic matter ðxXI Þ was negligible, while the initial fraction of inert soluble organic matter ðxSI Þ was 20.94% ` 1.65. A model with first-order serial-parallel reactions system was developed for biodegradable fractions. This model has demonstrated its capability to predict the behaviour of the system and can be used for further research work or more complex reactor design.